MODELING MULTI-CRITERIA DECISION-MAKING IN DYNAMIC NEUTROSOPHIC ENVIRONMENTS BASES ON CHOQUET INTEGRAL - Thong, Nguyen Tho; Giap, Cu Nguyen; Tuan, Tran Manh; Chuan, Pham Minh; Hoang, Pham Minh; Dong, Do Duc (Journal of Computer Science and Cybernetics, 2020)
Multi-attributes decision-making problem in dynamic neutrosophic environment is an open and highly-interesting research area with many potential applications in real life. The concept of the dynamic interval-valued neutrosophic set and its application for the dynamic decision-making are proposed recently, however the inter-dependence among criteria or preference is not dealt with in the proposed operations to well treat inter-dependence problems. Therefore, the definitions, mathematical operations and its properties are mentioned and discussed in detail.Then, Choquet integral-based distance between dynamic inteval-valued neutrosophic sets is defined and used to develop a new decision making model based on the proposed theory. A practical application of proposed approach is constructed and tested on the data of lecturers' performance collected from Vietnam National University (VNU) to illustrate the efficiency of new proposal.